Fundamental of Entrepreneurship ENT300 Magnolia Homestay / Eva Yin Anak Tet-Foot... [et.al] - Tet-Foot, Eva Yin; Abdullah, Nurul Sahira; Innit, Shareena Sian; Dosis, Cyinthia Markdila; Francis Guma, Vanessa Esmeralda (2016)
Magnolia Homestay is a business that for people who wish to improve their language skills and become familiar with the local lifestyles and gives tourists the opportunity to stay with a chosen family, interact and experiences the daily life homestay families. This business location is 11 , 1316, 94500 Lundu, Sarawak. Our main activities is culture and lifestyle of local people in Lundu. We form a partnership business nature where we have five members which is General Manager, Marketing Manager, Operations Manager, Administration Manager and Financial Manager. Hence, the profit will equally divided to each members according to their percentage contribution.